THE SANDY HILL LANDSCAPE (CORRIENTES, ARGENTINA) FROM LATE PLEISTOCENE TO THE PRESENT - Félix Ignacio Contreras; Silvina Andrea Contreras; Cecilia Romina Méndez; Mariana Noemí Baruzzo; Elsie Araseli Ojeda; Ivana Evelin Kovalsky (Boletín Geográfico)
The landscape is the sum of natural and human elements. The presence of these elements, their distribution and interaction are combined throughout time to give shape to a particular place. In this context, water plays a fundamental role in the configuration of sandy hills landscape in Corrientes province, both originally and the modeling evolving over time, nowadays manifested by spatial patterns. The aim of this paper is to show the evolution of sandy hill region from the late Pleistocene to the present. The results were obtained due to the comparisons between the environmental reconstructions of the paleontological studies and the current situation of the region, besides the application of spatial analysis with geographic information systems and the knowledge of their shallow lakes distribution, since they constitute the main natural element of the landscape. The Corrientes landscape described to the Late Pleistocene is very similar to current landscape mainly to the water availability and the vegetal distribution. Using digital elevation models a topographic gradient in the sandy hills was observed and it showed decreases from the Paraná River alluvial fan apex to its base, with E-W or NE-SW direction. The Sandy Hill Landscape of Corrientes is one of the most important regions of Argentina due to their density, quantity, and distribution of the shallow lakes on the landscape.